A Scenario Analysis of the Potential Effects of Decarbonization on the Profitability of the Energy-Intensive and Natural-Resource-Based Industries - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2021)
The decarbonization of the energy-intensive and natural-resourced-based industries is associated with large economic costs. In this paper, I explore how decarbonization may affect the profitability and market value of these industries and their ability to attract capital to fund their decarbonization. I also discuss the possibility of compensating for the investment costs through higher prices and enhanced productivity. I answer these questions using scenario analysis with a focus on the industries in the European Union and the United States. I find that the effects on profitability are likely to be modest despite relatively high investment costs.
Keywords: L60; L70; Q54; 330; decarbonization; energy-intensive; industry; profitability; investment